2014
DOI: 10.1159/000363037
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthetic Ursolic Acid Derivative IUA with Anti-Tumor Efficacy Against Osteosarcoma Cells via Inhibition of JNK Signaling Pathway

Abstract: Background: Osteosarcoma is the most common primary malignant bone tumor in children and adolescents and is characterized by frequent metastasis and resistance to chemotherapy. Because osteosarcoma cells are not highly susceptible to current chemotherapy drugs, new alternative strategies for the treatment of osteosarcoma are needed. This study was undertaken to investigate the inhibitory effects of a new synthetic ursolic acid derivative IUA on osteosarcoma cells and to explore its molecular mechanism. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This result indicates that the modification at C-28 and 3-OH in the UA core significantly increases the antitumor activities of UA. These results are consistent with a previous study by Chen et al ( 36 ), which demonstrated that the structural changes in position 3 and/or 28 of UA were crucial for its cytotoxic activity. In another study, UA-benzylidine derivatives exhibited strong cytotoxic activity and amino acid linkage ( 37 ), and UA also caused significant cytotoxic effects in different cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that the modification at C-28 and 3-OH in the UA core significantly increases the antitumor activities of UA. These results are consistent with a previous study by Chen et al ( 36 ), which demonstrated that the structural changes in position 3 and/or 28 of UA were crucial for its cytotoxic activity. In another study, UA-benzylidine derivatives exhibited strong cytotoxic activity and amino acid linkage ( 37 ), and UA also caused significant cytotoxic effects in different cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Ursolic acid displays various anticancer actions by reducing oncogene expression, modulating cell cycle, triggering apoptosis, suppressing metastasis, and regulating drug resistance (Zhang et al ., 2007; Manu and Kuttan, 2008; Lin et al ., 2013; Ou et al ., 2014; Xiang et al ., 2015). Ursolic acid derivatives such as FZU-03,010, ursolic acid-benzylidine, UP12, and IUA have been demonstrated as potent anticancer agents against hepatocellular carcinoma, osteosarcoma, lung, colon, and breast cancer cells (Chen et al ., 2014; Dong et al ., 2015; Dar et al ., 2016; Li et al ., 2017). However, the antitumor activity of ursolic acid derivatives in oral cancers has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the inhibitory activity of the leading compound 5b, we evaluated the proliferation inhibition effect of 5b against some other different cancer cell lines. The proliferation inhibition ability of 5b on MCF-7, MDA-MB-231, HT-29, LoVo, B16-F10, RL95-2, and SCL-1 cell lines was tested by MTT assay at different concentrations (1,5,10,20, and 40 lM) for 24 h. Compound 5b showed decreased cell viability in a dose-dependent manner. The IC 50 values of 5b against these cell lines were 7.05, 5.71, 9.40, 7.78, 6.79, 6.87, and 7.13 lM, respectively ( Table 2).…”
Section: Effect Of Ua-5b On Cell Viabilitymentioning
confidence: 99%
“…To improve its activity and bioavailability, structural modifications were performed on UA to discover potential anticancer agents . It has been reported that some of UA derivatives that modified at the 3‐OH and/or 17‐COOH positions exhibit significant antitumor effects both in vitro and in vivo . Previous studies in our laboratory showed that incorporation of N ‐(2‐hydroxyethyl) piperazine or 2‐methylpiperazine moiety at the C‐28 position of UA exhibited better inhibitory effect on growth of cancer cells .…”
mentioning
confidence: 99%